WWP2 regulates pathological cardiac fibrosis by modulating SMAD2 signaling - Chen, Huimei; Moreno-Moral, Aida; Pesce, Francesco; Devapragash, Nithya; Mancini, Massimiliano; Heng, Ee Ling; Rotival, Maxime; Srivastava, Prashant K; Harmston, Nathan; Shkura, Kirill; Rackham, Owen J L; Yu, Wei-Ping; et al. (Nature communications, 2019)
Cardiac fibrosis is a final common pathology in inherited and acquired heart diseases that causes cardiac electrical and pump failure. Here, we use systems genetics to identify a pro-fibrotic gene network in the diseased heart and show that this network is regulated by the E3 ubiquitin ligase WWP2, specifically by the WWP2-N terminal isoform. Importantly, the WWP2-regulated pro-fibrotic gene network is conserved across different cardiac diseases characterized by fibrosis: human and murine dilated cardiomyopathy and repaired tetralogy of Fallot. Transgenic mice lacking the N-terminal region of the WWP2 protein show improved cardiac function and reduced myocardial fibrosis in response to pressure overload or myocardial infarction. In primary cardiac fibroblasts, WWP2 positively regulates the expression of pro-fibrotic markers and extracellular matrix genes. TGFβ1 stimulation promotes nuclear translocation of the WWP2 isoforms containing the N-terminal region and their interaction with SMAD2. WWP2 mediates the TGFβ1-induced nucleocytoplasmic shuttling and transcriptional activity of SMAD2.
Keywords: dospělí; myši transgenní; Animals; Extracellular Matrix Proteins; Female; Adult; Mice, Transgenic; ženské pohlaví; mladý dospělý; Fibrosis; genové regulační sítě; protein Smad2; Transforming Growth Factor beta; Adolescent; lidé; kardiomyopatie; Mice; transformující růstový faktor beta; genetická predispozice k nemoci; Heart Diseases; Gene Regulatory Networks; Genetic Predisposition to Disease; myši; Smad2 Protein; Humans; regulace genové exprese; Male; ubikvitinligasy; Aged; extracelulární matrix - proteiny; Protein Isoforms; Young Adult; Cardiomyopathies; lidé středního věku; senioři; zvířata; mužské pohlaví; protein - isoformy; Gene Expression Regulation; Ubiquitin-Protein Ligases; fibróza; Middle Aged; mladiství; nemoci srdce